1997
DOI: 10.1103/physrevc.55.431
|View full text |Cite
|
Sign up to set email alerts
|

Strangeness in the nucleon on the light cone

Abstract: Strange matrix elements of the nucleon are calculated within the light-cone formulation of the meson cloud model. The Q 2 dependence of the strange vector and axial vector form factors is computed, and the strangeness radius and magnetic moment extracted, both of which are found to be very small and slightly negative. Within the same framework one finds a small but nonzero excess of the antistrange distribution over the strange at large x. Kaon loops are unlikely, however, to be the source of a large polarized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 55 publications
9
75
0
Order By: Relevance
“…Future higher-quality neutrino DIS data should help establish the sign and magnitude of this asymmetry. Finally, strange chiral loops can also lead to nonzero values for strange electric and magnetic form factors [36]. The magnitude of the kaon cloud contributions, although rather small, is consistent with that of the available data [37].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Future higher-quality neutrino DIS data should help establish the sign and magnitude of this asymmetry. Finally, strange chiral loops can also lead to nonzero values for strange electric and magnetic form factors [36]. The magnitude of the kaon cloud contributions, although rather small, is consistent with that of the available data [37].…”
Section: Resultssupporting
confidence: 69%
“…As originally noticed by Signal and Thomas [35], virtual kaon loops are one possible source of nonperturbative strangeness in the nucleon [36]. This has also been placed on a firm footing by observing that the moments of the difference between the s ands distributions in the nucleon are nonanalytic functions of m q +m s , with m s the strange quark mass, leading to model-independent predictions for the asymmetry between s ands in the nucleon sea.…”
Section: Resultsmentioning
confidence: 81%
“…The difference between the s and s distributions determined by the CCFR collaboration [22] has been studied in the context of meson cloud models [109,110,111,112] and has been modeled by gluon splitting into s and s quarks with different effective masses [107]. Meson cloud models tend to produce larger differences between s(x) and s(x) than can be accommodated by the data, leading Ji and Tang to suggest that the strange sea is highly localized [107].…”
Section: Strange Sea Summarymentioning
confidence: 99%
“…Using a light-front formalism that enabled simultaneous computation of strange observables in both deep-inelastic and elastic scattering, the small experimental values of the strange electromagnetic form factors were found [28,29] to restrict the magnitude of s −s to be very small, with a shape strongly dependent on the choice of the N KY vertex function. Cao and Signal [30] later observed that while fluctuations to KΛ and KΣ states gave rise to a small positive asymmetry, S − = 0.143 × 10 −3 , the inclusion of the heavier K * mesons [31] changed the sign of the overall asymmetry, S − = −0.135 × 10 −3 , with the magnitude remaining rather small.…”
Section: Introductionmentioning
confidence: 99%